2010
DOI: 10.1021/jo101240s
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Chlorosulfonyl Isocyanate with Fluorosubstituted Alkenes: Evidence of a Concerted Pathway

Abstract: Concerted reactions are indicated for the electrophilic addition of chlorosulfonyl isocyanate with monofluoroalkenes. A vinyl fluorine atom on an alkene raises the energy of a stepwise transition state more than the energy of the competing concerted pathway. This energy shift induces CSI to react with monofluoroalkenes by a one-step process. The low reactivity of CSI with monofluoroalkenes, stereospecific reactions, the absence of 2:1 uracil products with neat fluoroalkenes, and quantum chemical calculations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 42 publications
(33 reference statements)
4
15
1
Order By: Relevance
“…However, in this work, we introduce a new mechanism by providing computational evidence for the asynchronous concerted pathway for the first addition step of epoxides to CSI. Previous computational studies [37,47] involve reactions of CSI with substrates other than epoxides and therefore they are not directly comparable to our reaction; however, they proposed that the reactions of isocyanates may take place through a concerted mechanism. These results are consistent with our computational findings.…”
Section: Formation Of Oxazolidinone 9fcontrasting
confidence: 56%
See 2 more Smart Citations
“…However, in this work, we introduce a new mechanism by providing computational evidence for the asynchronous concerted pathway for the first addition step of epoxides to CSI. Previous computational studies [37,47] involve reactions of CSI with substrates other than epoxides and therefore they are not directly comparable to our reaction; however, they proposed that the reactions of isocyanates may take place through a concerted mechanism. These results are consistent with our computational findings.…”
Section: Formation Of Oxazolidinone 9fcontrasting
confidence: 56%
“…To the best of our knowledge, there is no computational mechanistic study in the literature regarding the reaction of epoxides with CSI. On the other hand, the reactions of isocyanates with monofluoroalkenes and nitrones were modeled with the Møller-Plesset (MP2) perturbation theory and M06-2X functional, respectively [37,47]. According to these computational studies, such reactions of isocyanates may proceed through a concerted pathway.…”
Section: Keshava Murthy and Dharmentioning
confidence: 99%
See 1 more Smart Citation
“…Shellhamer et al [37] explored the reaction mechanism of monofluoroalkenes with CSI using Møller-Plesset (MP2) perturbation theory (Scheme 3). Their results showed that the concerted mechanism is preferred over the stepwise pathway.…”
Section: Scheme 2 Proposed Mechanisms By Murthy Dharmentioning
confidence: 99%
“…CSI, an highly reactive and versatile isocyanate, reacts with epoxides to give five-membered cyclic carbonates and oxazolidinones [37][38][39]. In 1984, Keshava Murthy and Dhar reported the synthesis of five-membered cyclic carbonates and oxazolidinones from various epoxides in two steps using CSI and KOH in benzene:dichloromethane (5:1) [40,41].…”
Section: Introductionmentioning
confidence: 99%